POLLUTION LEVELS OF AIR HITAM RIVER IN TOFU INDUSTRY AREA PEKANBARU BASED ON WATER QUALITY AND MACROZOOBENTHOS - Abdi Anwar Lubis; Sampe Harahap; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Air Hitam River is one of the most polluted river in Pekanbaru, as there is a tofu industry and households that discharge the waste to the river. To understand the pollution level of the river, a study has been conducted from March to April 2015. The pollution level was identified based on water quality and macrozoobenthos community structure in the river. There were 4 stations and 3 sampling points in each station. Water samples were taken 3 times, once a week and water quality parameters measured were temperature, current speed, TSS, depth, pH, BOD5, COD and ammonia. While the macrozoobenthos diversity (H’) was analyzed usinga Shannon-Weinermethod. Results shown that temperature was 27.67 – 28.00 0C, current speed: 13.00 – 35.00 cm/sec, TSS: 28.66 – 51.86 mg/L, depth 47.33 – 75.33 cm, pH: 5, BOD5: 5.61 – 12.51 mg/L, COD: 29.60 – 38.70 mg/L, ammonia: 1.610 – 3.389 mg/L. The value of the TSS, BOD5, COD and ammonia were higher than those of the Quality Standard PP No 82/2001 and the H’ of the macrozoobentos was 0.93 – 1.802. Based on data obtained, it can be concluded that the Air Hitam River was lightly to heavily polluted.Keywords: Air Hitam River, Water Quality, Macrozoobenthos, Tofu Liquid Waste